AUTENTIFIKASI DAN INFILTRASI DALAM TAFSIR ISHĀRĪ - Husna, Rifqatul (Universitas Nurul Jadid, 2021)
The ishārī interpretation is one of the style or form in the tafsir studies. On the one hand, ishāri was considered to have a positive impact on the interpretation of the al-Qur’an and on the other hand, it was considered a deviant kind of interpretation from al-maqāsid al-shar’iyyah or even contrary to the al-Qur’an and hadīth as the main source in interpreting the al-Qur’an. Therefore, scholars make provisions, criteria, and requirement in interpretation. The mufassir classifies what is considered the main (al-asīl) or basis in an interpretation, and which is considered as abuses (al-dakhīl) in an interpretation. From this academic problem, the discipline of al-asīl wa al-dakhīl fi al-tafsīr was emergent. This research aims to aim to discovere out meeting point the ishāri interpretation, whether it is true or worthy of being considered as al-dakhīl in interpretation or is it necessary to reconstruct the definition, type, or division in the knowledge of al-asīl and al-dakhīl? This study uses the content analysis method so that discussions and conclusions can be traced so that it can produce a neat and orderly conclusion, which in turn results in a conclusion that the ishārī interpretation will be considered and categorized as al-asīl if it meets several conditions: a) the interpretation does not contradict the meaning of zahir the end of the verse, b) the interpretation must not contradict reason and sharī'ah, and c) between the interpretation and the interpretation interpreted there is a relationship and correlation.